Studying the Ways to Reduce the Harmful Effects of Plastic Bottles in Municipal Solid Waste on the Environment in Small Towns - BAYAZITOVA, Zulfiya E.; ZHAPAROVA, Sayagul B.; MUKHAMADEYEVA, Railya M.; TLEUOVA, Zhulduz O.; MAKEEVA, Lyudmila A.; YELYUBAYEV, Sagintay Z. (Journal of Environmental Management and Tourism; Vol 7 No 3 (2016): JEMT Volume VII Issue 3(15) Fall 2016, 2016)
The study was aimed at solving the following problems: lessening the negative effects of human activities on the environment, reducing the territories covered by municipal solid waste landfills (MSWLFs), and creating preconditions for the formation of infrastructure for plastic bottles recycling. A map of landfills registered in the territory of Akmola region Republic of Kazakhstan has been developed, and field studies of their morphological and fractional composition were conducted with the help of “ERA” software. During the research, the authors have applied a public opinion poll, an anonymous questionnaire and an expert assessment. The method of weight characteristics was used to choose the optimal way. As opposed to the methods of information processing used by the specialized company Credit Suisse, the employed methods allowed for the mentality of the local population. Based on the findings of the research, the authors have arrived at the following conclusions: the problem of relieving the workload on municipal solid waste landfills will become increasingly acute, and collection and recycling of plastic packaging can serve as one of the ways to decrease the amount of municipal solid waste (MSW). A novel integrated study of MSWLFs of small cities was carried out, and recommendations on collecting plastic bottles in urban areas with the population of 50,000 or less were given.
Keywords: polyethylene terephthalate; recycling; plastic packaging; municipal solid waste separation